Influence of cutting parameters on wear of diamond wire during multi-wire rocking sawing with reciprocating motion - Yang, Zixing; Huang, Hui; Liao, Xinjiang (Frontiers in Mechanical Engineering, 2022)
Multi-wire cutting with diamond wire saw has gradually become the main processing method for hard-and-brittle materials due to its small kerf loss and high machining accuracy. However, the diamond wire saw will inevitably suffer wear during the process of machining, and hence affects the quality of the cut surface. In this paper, a wire saw wear model was established, and the wear at different positions on the wire saw was theoretically calculated by correlating the volume of the workpiece removed by the unit wire saw to the wire saw wear. The iteration method was used to calculate the wear of the wire saw after cutting by superimposing the wear caused by every monolithic wafer. Based on this wear model of wire saw, the influence of multi-wire cutting parameters and the shapes of the workpiece on the wire saw wear was discussed through numerical simulation. The simulation results showed that the feed speed of the workpiece and the length of the wire saw had an obvious effect on the maximum wear of the wire saw, and the maximum rocking angle,wire speed and reciprocating times had little effect on the maximum wear of the wire saw. The wear curve of the circular workpiece wire saw is unstable in the whole process, and the wear curve of the rectangular workpiece wire saw changes at the beginning and end, and the middle is stable.